2017
DOI: 10.1002/2017je005331
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Alteration of Ferrous Smectites and Implications for the Redox Evolution of Early Mars

Abstract: Surface conditions on early Mars were likely anoxic, similar to early Earth, but the timing of the evolution to oxic conditions characteristic of contemporary Mars is unresolved. Ferrous trioctahedral smectites are the thermodynamically predicted products of anoxic basalt weathering, but orbital analyses of Noachian‐aged terrains find primarily Fe3+‐bearing clay minerals. Rover‐based detection of Fe2+‐bearing trioctahedral smectites at Gale Crater suggests that ferrous smectites are the unoxidized progenitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
64
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(78 citation statements)
references
References 114 publications
13
64
1
Order By: Relevance
“…Conformable units below VRR and the Blunts Point member contain abundant smectite (Bristow et al, 2018), and units that are stratigraphically equivalent to Jura in the Glen Torridon locale to the south of VRR contain the most smectite observed to date (Bristow et al, 2019). Fe‐bearing smectite alteration on VRR could result in a relatively low abundance of phyllosilicate on VRR, in addition to precipitation of Fe oxides and oxyhydroxides from the Fe present in the smectite structure and the precipitation of opaline silica from leaching of silica from clay mineral tetrahedral layers (e.g., Chemtob et al, 2017; Sherman et al, 1962).…”
Section: Discussionmentioning
confidence: 99%
“…Conformable units below VRR and the Blunts Point member contain abundant smectite (Bristow et al, 2018), and units that are stratigraphically equivalent to Jura in the Glen Torridon locale to the south of VRR contain the most smectite observed to date (Bristow et al, 2019). Fe‐bearing smectite alteration on VRR could result in a relatively low abundance of phyllosilicate on VRR, in addition to precipitation of Fe oxides and oxyhydroxides from the Fe present in the smectite structure and the precipitation of opaline silica from leaching of silica from clay mineral tetrahedral layers (e.g., Chemtob et al, 2017; Sherman et al, 1962).…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Catalano () and Chemtob et al. () suggest that the low abundance of ferrous phyllosilicates might be a result of postformational oxidation with formation of ferric smectites, rather than original formation in an oxidizing environment. Moreover, Catalano () suggested that the scarce hydrous Al‐bearing silicate identifications on Mars might indicate that subsurface alteration at elevated temperature is an unlikely scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Strongly reducing conditions in terrestrial hydrothermal systems has been postulated as a source for hydrogen production observed in the Yellowstone National Park and in the Columbia River Basalt McKinley 1995, 2000;Spear et al 2005). Studies by Catalano (2013) and Chemtob et al (2017) suggest that the low abundance of ferrous phyllosilicates might be a result of postformational oxidation with formation of ferric smectites, rather than original formation in an oxidizing environment. Moreover, Catalano (2013) suggested that the scarce hydrous Al-bearing silicate identifications on Mars might indicate that subsurface alteration at elevated temperature is an unlikely scenario.…”
Section: Martian Implicationsmentioning
confidence: 99%
“…Alternatively, the observed smectites could be detrital and represent chemical weathering products from a source region supplying sediment to the lake. In this scenario, the variable di:tri ratios could reflect changes in weathering signatures from the source or along the fluid pathway, or different mixtures of detrital and authigenic clays (e.g., Chemtob et al, 2015Chemtob et al, , 2017Mangold et al, 2018).…”
Section: Journal Of Geophysical Research: Planetsmentioning
confidence: 99%